THE EFFECTIVENESS OF DEVELOPING LOCAL CULTURE-BASED FLIPBOOK TEACHING MATERIALS TO INCREASE STUDENTS' LEARNING MOTIVATION - Nasution, Muhammad Iqbal (FKIP Universitas Muhammadiyah Tangerang, 2024)
This study aims to determine the effectiveness of mathematics teaching materials in the form of flipbooks based on local culture in Percut Sei Tuan District on quadrilateral and triangle material in class VII of Pusaka Junior High School in B. Klippa village to increase students' learning motivation. This type of research is development research that refers to the Hannafin and Peck development model which consists of 3 stages, namely: the needs assessment stage, the design stage, and the development/implementation stage. After the teaching materials are declared valid, they are used in the implementation stage. Based on the measurement of learning motivation before and after using flipbook teaching materials, it can be concluded that the development of flipbook teaching materials can increase student learning motivation with an increase of 8,28% from 78.67% to 86.95%. Based on criteria for the effectiveness of teaching materials, teaching materials effective in increasing students’learning motivation because 80% of the students gave positive responses to teaching materials.